Supporting strategic health purchasing: A case study of annual health budgets from general tax revenue and social health insurance in Abia state, Nigeria - Chinyere Mbachu; Chinyere Okeke; Chinonso Obayi; Agnes Gatome-Munyua; Nkechi Olalere; Ikechi Ogbonna; Benjamin Uzochukwu; Obinna Emmanuel Onwujekwe (Health Economics Review, 2021)
Background: Tracking general trends in strategic purchasing of health financing mechanisms will highlight where country demands may exist for technical support and where progress in being made that offer opportunities for regional learning. Health services in Abia State, Nigeria are funded from general tax-revenues (GTR), and a new state social health insurance scheme (SSHIS) is proposed to overcome the failings of the GTR and expand coverage of services. This study examined purchasing functions within the GTR and the proposed SSHIS to determine if the failings in GTR have been overcome, identify factors that shape health purchasing at sub-national levels, and provide lessons for other states in Nigeria pursuing a similar intervention. Methods: Data was collected through document review and key informant interviews. Government documents were retrieved electronically from the websites of different organizations. Hard copies of paper-only files were retrieved from relevant government agencies and departments. Interviews were conducted with seven key personnel of the State Ministry of Health and State Health Insurance Agency. Thematic analysis of data was based on a strategic health purchasing progress tracking framework which delves into the governance arrangements and information architecture needed for purchasing to work well; and the core purchasing decisions of what to buy; who to buy from; and how to buy. Results: There are differences in the purchasing arrangements of the two schemes. Purchaser-provider split does not exist for the GTR, unlike in the proposed SSHIS. There are no data systems for monitoring provider performance in the GTR-funded system, unlike in the SSHIS. Whereas GTR is based on a historical budgeting system, the SSHIS proposes to use a defined benefit package, which ensures value-for-money, as the basis for resource allocation. The GTR lacks private sector engagement, provider accreditation and contracting arrangements while the SSHIS will accredit and engage private providers through selective contracting. Likewise, provider payment is not linked to performance or adherence to established standards in the GTR, whereas provider payment will be linked to performance in the SSHIS. Conclusions: The State Social Health Insurance has been designed to overcome many of the limitations of the budgetary allocation to health. This study provides insights into the enabling and constraining factors that can be used to develop interventions intended to strengthen the strategic health purchasing in the study area, and lessons for the other Nigeria states with similar characteristics and approaches.
Keywords: 330; Strategic health purchasing; SHP; Social health insurance; Annual budgets